Spermidine Retarded the Senescence of Multipotent Mesenchymal Stromal Cells In Vitro and In Vivo through SIRT3-Mediated Antioxidation - Hua Huang; Wen Zhang; Junjie Su; Bisheng Zhou; Qingjiang Han (Stem Cells International)
Multipotent mesenchymal stromal cells (MSCs) expand in vitro and undergo replicative senescence, thereby restricting their clinical utilization. Thus, an effective strategy is required to impede MSC senescence. Since spermidine (SPD) supplementation can prolong the lifespan of yeast by inhibiting oxidative stress, spermidine is a potential option for delaying MSC senescence. In this study, to test our hypothesis, we first isolated primary human umbilical cord mesenchymal stem cells (hUCMSCs). Subsequently, the appropriate SPD dose was administered during continuous cell cultivation. Next, we evaluated the antisenescence effects by SA-β-gal staining, Ki67 expression, reactive oxygen species (ROS) levels, adipogenic or osteogenic ability, senescence-associated markers, and DNA damage markers. The results revealed that early SPD intervention significantly delays the replicative senescence of hUCMSCs and constrains premature H2O2-induced senescence. Additionally, by silencing SIRT3, the SPD-mediated antisenescence effects disappear, further demonstrating that SIRT3 is necessary for SPD to exert its antisenescence effects on hUCMSCs. Besides, the findings of this study also suggest that SPD in vivo protects MSCs against oxidative stress and delays cell senescence. Thus, MSCs maintain the ability to proliferate and differentiate efficiently in vitro and in vivo, which reflects the potential clinical utilization of MSCs in the future.